Upaya guru dalam Mengembangkan Keterampilan komunikasi anak dengan Speech Delay di TK Nurul Bilad - Ayunda, Puja (Literal: Disability Studies Journal, 2024)
Speech delays can hinder children's social interaction and emotional development, making teacher intervention essential. Through a qualitative research approach, this study reveals teachers' strategies for developing communication in children with speech delay at the early childhood education level. The subjects in this study amounted to 3 children aged 5 years. The research was conducted at Nurul Bilad Kindergarten for 12 months. Data were collected using observation, interview and documentation study techniques. Data analysis used the stages of Miles & Huberman, namely data reduction, data display, and conclusion drawing. Data validity was ensured by researcher persistence, member check, and triangulation. The results of the study showed that the active involvement of teachers in monitoring and supporting children's communication processes not only improved their speaking skills, but also increased their self-confidence and social interaction. Data triangulation used multiple data sources including interviews, documents and observations to verify the information. Thus, the role of teachers is crucial in helping children with speech delay to adapt and thrive in their social context. The findings are expected to provide insights for educators and parents in supporting children's communication development.